Hydrocephalus in Spinal Muscular Atrophy: A Case Report and Review of the Literature - Sah, Jeetendra P.; Abrams, Aaron W.; Chari, Geetha; Linden, Craig; Anziska, Yaacov (Journal of Pediatric Neurology, 2020)
In this article, we reported a case of spinal muscular atrophy (SMA) type I noted to have tetraventricular hydrocephalus with Blake's pouch cyst at 8 months of age following intrathecal nusinersen therapy. The association of hydrocephalus with SMA is rarely reported in the literature. Development of hydrocephalus after intrathecal nusinersen therapy is also reported in some cases, but a cause–effect relationship is not yet established. The aim of this study was to describe the clinical characteristics of a patient with SMA type I and hydrocephalus, to review similar cases reported in the literature, and to explore the relationship between nusinersen therapy and development of hydrocephalus. The clinical presentation and radiographic findings of the patient are described and a comprehensive review of the literature was conducted. The adverse effect of communicating hydrocephalus related to nusinersen therapy is being reported and the authors suggest carefully monitoring for features of hydrocephalus developing during the course of nusinersen therapy.
Keywords: spinal muscular atrophy; hydrocephalus; nusinersen; Blake's pouch cyst